2020
DOI: 10.1007/s13668-020-00313-5
|View full text |Cite|
|
Sign up to set email alerts
|

Probiotics and the Microbiota-Gut-Brain Axis: Focus on Psychiatry

Abstract: Purpose of Review Probiotics are living bacteria, which when ingested in adequate amounts, confer health benefits. Gut microbes are suggested to play a role in many psychiatric disorders and could be a potential therapeutic target. Between the gut and the brain, there is a bi-directional communication pathway called the microbiota-gut-brain axis. The purpose of this review is to examine data from recent interventional studies focusing on probiotics and the gut-brain axis for the treatment of depression, anxiet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
152
1
15

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 219 publications
(169 citation statements)
references
References 91 publications
(108 reference statements)
1
152
1
15
Order By: Relevance
“…In a recent meta-analysis, 19 double-blind, randomized, placebo-controlled trials on the effect of probiotics on depressive symptoms were published between 2010 and 2019 [17,18]. Notably, only three of them included individuals with major depressive disorder (MDD) [19][20][21], while the other studies were conducted with healthy controls or other clinical populations (e.g., irritable, bowel syndrome, diabetes with coronary heart disease, fibromyalgia) [6,13,15,17,18]. Akkasheh et al [19] included 40 patients with MDD (age 20-55 years) receiving an eight-week intervention with Lactobacillus (L.) acidophilus, L. casei and Bifidobacterium (B.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent meta-analysis, 19 double-blind, randomized, placebo-controlled trials on the effect of probiotics on depressive symptoms were published between 2010 and 2019 [17,18]. Notably, only three of them included individuals with major depressive disorder (MDD) [19][20][21], while the other studies were conducted with healthy controls or other clinical populations (e.g., irritable, bowel syndrome, diabetes with coronary heart disease, fibromyalgia) [6,13,15,17,18]. Akkasheh et al [19] included 40 patients with MDD (age 20-55 years) receiving an eight-week intervention with Lactobacillus (L.) acidophilus, L. casei and Bifidobacterium (B.)…”
Section: Introductionmentioning
confidence: 99%
“…Improvements in depressive symptoms were significantly higher in individuals with MDD treated with probiotics than in those receiving placebo in patients (for a review see [18]). In another review [22], one more study has been identified including an intervention with probiotics compared to placebo in 60 individuals with depression [23].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we recently reported RA-triggered monoamine increase in the brain, and inhibition of Aβ aggregation by monoamines in mice fed with RA 9 ; however, RA concentrations in the brain of these mice 8 , 9 were undetectable. Another possibility is that RA might act on peripheral targets such as gastrointestinal tract, which might contribute to prevention of the worsening of neuropsychiatric symptoms 27 .…”
Section: Discussionmentioning
confidence: 99%
“…To date, studies in humans have focused on characterising microbe populations in both health and disease 4 , 13 . In adults the gut microbiota has been related to atypical social functioning in autism 14 and symptoms of anxiety and depression 7 , 15 , 16 . Animal research has suggested that the gut microbiota plays an important role during key moments in the host development, in particular during adolescence, which represents a critical time window where gut microbiota help fine-tune the gut–brain axis 2 , 8 , 17 , 18 .…”
Section: Introductionmentioning
confidence: 99%